Effects of 4-nitrophenol on expression of the ER-α and AhR signaling pathway-associated genes in the small intestine of rats. (September 2016) - Tang, Juan; Song, Meiyan; Watanabe, Gen; Nagaoka, Kentaro; Rui, Xiaoli; Li, ChunMei
Abstract: 4-Nitrophenol (PNP) is a persistent organic pollutant that was proven to be an environmental endocrine disruptor. The aim of this study was to evaluate the role of the estrogen receptor-α (ER-α) and aryl hydrocarbon receptor (AhR) signaling pathway in regulating the damage response to PNP in the small intestine of rats. Wistar-Imamichi male rats (21 d) were randomly divided into two groups: the control group and PNP group. Each group had three processes that were gavaged with PNP or vehicle daily: single dose (1 d), repeated dose (3 consecutive days) (3 d), and repeated dose with recovery (3 consecutive days and 3 recovery days) (6 d). The weight of the body, the related viscera, and small intestine were examined. Histological parameters of the small intestine and the quantity of mucus proteins secreted by small goblet cells were determined using HE staining and PAS staining. The mRNA expression of AhR, ER-α, CYP1A1, and GST was measured by real-time qPCR. In addition, we also analyzed the AhR, ER-α, and CYP1A1 expression in the small intestine by immunohistochemical staining. The small intestines histologically changed in the PNP-treated rat and the expression of AhR, CYP1A1, and GST was increased. While ER-α was significantly decreased in the small intestine, simultaneously, when rats were exposed to a longer PNP treatment, the damages disappeared. Our results demonstrate that PNP has an effect on the expression of AhR signaling pathway genes, AhR, CYP1A1, and GST, and ER-α in the rat small intestine. Highlights: PNP treatment caused marked damage in the small intestine. The damage caused by PNP on the small intestine was related to the ERα and AhR signaling pathway associated genes. The damage can be attenuated after termination of PNP treatment on the small intestine. Abstract : PNP treatment caused marked damage in the small intestine. The damage caused by PNP on the small intestine was related to the ERα and AhR signaling pathway associated genes.